2016
DOI: 10.1242/jcs.174920
|View full text |Cite
|
Sign up to set email alerts
|

A novel high-content analysis tool reveals Rab8-driven cytoskeletal reorganization through Rho GTPases, calpain and MT1-MMP

Abstract: Rab8 is a small Ras-related GTPase that regulates polarized membrane transport to the plasma membrane. Here, we developed a high-content analysis (HCA) tool to dissect Rab8-mediated actin and focal adhesion reorganization that revealed that Rab8 activation significantly induced Rac1 and Tiam1 to mediate cortical actin polymerization and RhoA-dependent stress fibre disassembly. Rab8 activation increased Rac1 activity, whereas its depletion activated RhoA, which led to reorganization of the actin cytoskeleton. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 61 publications
2
32
0
1
Order By: Relevance
“…In agreement with earlier studies, we found that in HT 1080 cells grown on collagen-coated dishes, export of MMP14 was inhibited by overexpression of Rab8a T22N ( Fig. 8 A; Bravo-Cordero et al, 2016Wiesner et al, 2013). It was also inhibited by Rab10 T23N, MICAL1 G3W, GRAF1/2 BAR-PH, and WDR44 ΔC.…”
Section: Mical1 Connects Graf1b/2 To Rab8 and Rab10supporting
confidence: 92%
“…In agreement with earlier studies, we found that in HT 1080 cells grown on collagen-coated dishes, export of MMP14 was inhibited by overexpression of Rab8a T22N ( Fig. 8 A; Bravo-Cordero et al, 2016Wiesner et al, 2013). It was also inhibited by Rab10 T23N, MICAL1 G3W, GRAF1/2 BAR-PH, and WDR44 ΔC.…”
Section: Mical1 Connects Graf1b/2 To Rab8 and Rab10supporting
confidence: 92%
“…57 Most recently, Rab8 activation has been shown to induce Rac1 activity, causing cortical actin formation, focal adhesion disassembly, and stress fiber disassembly. 58 This effect was dependent on Calpain, MT1-MMP, and Rho GTPases. 58 Furthermore, Rab8 is necessary for persistent cell motility, as well as EGFinduced polarity and chemotaxis.…”
Section: Molecular Control Of Calcium Influxes Upon Induction Of Epitmentioning
confidence: 97%
“…58 Furthermore, Rab8 is necessary for persistent cell motility, as well as EGFinduced polarity and chemotaxis. 58 These data all point to a direct link between the slow endocytic recycling pathway and initiation of cellular motility required for EMT. Additionally, it shows Rab8 affects RhoA activity.…”
Section: Molecular Control Of Calcium Influxes Upon Induction Of Epitmentioning
confidence: 99%
“…In fact, FIP3 silencing induced T-cell spreading, a process that is controlled by Rac1, suggesting endosomal trafficking of Rac1 to regulate T-cell spreading and activation in the immunological synapse [131]. Finally, Rab8, which localizes to the endocytic recycling compartment, was demonstrated to increase Rac1 activity and Tiam1/Rac1 mobilization from intracellular compartments to cortical locations to maintain directionality of migrating cells by enabling focal adhesion turnover and actin polymerization [132]. Combined, these studies suggest that endosomal trafficking routes are major determinants of Rac activity patterns emanating from the PM.…”
Section: Rho Gtpases Acting Along the Endocytic Pathwaymentioning
confidence: 96%